A case of hard-to-diagnose Papuloerythroderma of Ofuji in an elderly male - Yusharyahya, Shannaz Nadia; Yasmin, Farah Asyuri; Ryan, Elisabeth; Legiawati, Lili; Astriningrum, Rinadewi; Rihatmadja, Rahadi (Journal of Pakistan Association of Dermatologists, 2023)
Papuloerythroderma of Ofuji (PEO) is a rare form of dermatosis, frequently regarded as a diagnosis of exclusion. The clinical manifestation comprises brownish-red flat papules characteristically sparing the skin fold area, giving the tell-tale â€œdeck chairâ€ sign. Despite the distinctive presentation, many PEO cases are relatively difficult to be recognized, owing to the largely nonspecific clinical and histopathologic features. Various conditions, including atopy, infection, medication, and malignancy, especially cutaneous T-cell lymphoma (CTCL), are often associated with the disease. Herein we described an elderly Indonesian male with erythematous plaques on the head and trunk initially diagnosed as psoriasis vulgaris, in whom PEO was established after two months of evaluation. Treatment with oral cyclosporine and methylprednisolone resulted in clinical improvement. This case illustrates that albeit rare, PEO, and more importantly CTCL, need to be ruled out in this particular demographic setting.